Features of the subjective civil rights on patent - Iasechko, Svitlana; Skomorovskyi, Vitalii B.; Andronov, Ihor; Zaitsev, Oleksii; Bortnik, Oksana; Скоморовський, Віталій Богданович; Скоморовський, Віталій (Innovare Academics Sciences Pvt. Ltd, 2020)
The main aspects of the impact of patents on technological and social development have been highlighted, and it has been suggested to adapt a powerful world experience in this field. The key aspects of the innovation process and the protection of the results of scientific and technical action with the help of patents, and the peculiarities of the occurrence of subjective civil rights are considered
Keywords: invention; patent; patenting; subjective rights; technological development; technology